English for academic purposes : - Hyland, Ken (Routledge, 2006)
This book "introduces the major theories, approaches and controversies in the field. [It] gathers together influential readings from key names in the discipline, including: John Swales, Alastair Pennycook, Greg Myers, Brian Street and Ann Johns. [It] provides numerous exercises as practical study tools that encourage in students a critical approach to the subject. Written by an experienced teacher and researcher in the field, 'English for academic purposes' is an essential resource for students and researchers of applied linguisitics."